2021
DOI: 10.3390/s21175762
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Wound Area Measurement with Mobile Devices

Abstract: Healthcare treatments might benefit from advances in artificial intelligence and technological equipment such as smartphones and smartwatches. The presence of cameras in these devices with increasingly robust and precise pattern recognition techniques can facilitate the estimation of the wound area and other telemedicine measurements. Currently, telemedicine is vital to the maintenance of the quality of the treatments remotely. This study proposes a method for measuring the wound area with mobile devices. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…This increase in productivity and decision-making accuracy will undoubtedly improve patient care quality. In terms of efficiency, tools like Clinicgram®, or others [18,19,20,21,22,23] provides capabilities for the practical analysis of the cost-effectiveness of different treatments, as well as the generation of ratios that can reveal the real use of these treatments and their related costs.…”
Section: Discussionmentioning
confidence: 99%
“…This increase in productivity and decision-making accuracy will undoubtedly improve patient care quality. In terms of efficiency, tools like Clinicgram®, or others [18,19,20,21,22,23] provides capabilities for the practical analysis of the cost-effectiveness of different treatments, as well as the generation of ratios that can reveal the real use of these treatments and their related costs.…”
Section: Discussionmentioning
confidence: 99%
“…The main limitations of this study are related to its retrospective nature, the possibility of selection bias and the subjective assessment of the outcome. Many approaches have been proposed to assess wound healing, varying from a simple measurement with tape or calliper to more complex methods using digital cameras or a three‐dimensional measurement device 21–23 . However, these latter methods are expensive and not validated for primary closure.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings showed that clinicians successfully captured quality images of the wounds on the first attempt, 16.5% more often with Swift than manual methods. Evidence shows that quality images are essential to accurately measuring the wound area and tracking wound progress [ 7 ], an attribute that can support successful pre-authorization claims [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings showed that clinicians successfully captured quality images of the wounds on the first attempt, 16.5% more often with Swift than manual methods. Evidence shows that quality images are essential to accurately measuring the wound area and tracking wound progress [7], an attribute that can support successful pre-authorization claims [32]. Unlike Swift's application, using standard digital cameras to capture wound images can present challenges in capturing quality images due to a lack of image calibration that accounts for variable lighting conditions, skin tones and distance the picture is taken from the wound.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation